PEMANFAATAN PATI SAGU DAN TEPUNG IKAN PATIN DALAM PEMBUATAN BISKUIT - SESMITA SARI; VONNY SETIARIES JOHAN; AKHYAR ALI (Jurnal Sagu, 2016)
The objectives of this research was to obtain the best ratio of sago starch and catfish flour in making biscuitand meet the quality standard of biscuits (SNI 01-2973-1992). This research used a completely randomizeddesign (CRD) with 5 treatments and 4 replications. The treatments in this research were ratio of sago starchand catfish flour; SP1 (80 : 20), SP2 (70 : 30), SP3 (60 : 40), SP4 (50 : 50) and SP5 (40 : 60). The data obtainedwas analyzed statistically using analysis of variance and further tested with DNMRT at the level of 5%. Theresult showed the different combination of sago starch and catfish flour gave significant effect on the moisturecontent, ash content, protein content, fat content, colour, aroma, texture and taste of biscuit using descriptivetest. Based on the overall assessment, the panelists lightly like biscuit of all treatments. The best treatment ofthis research was biscuit with ratio sago starch 40 and catfish flour 60, which moisture content 3.55%, ashcontent 1.36%, protein content 27.33%, fat content 8.88% and met quality standard of biscuit (SNI 01-2973-1992). The biscuit have characteristics cream in colour, the aroma was fishy, little brittle and tasted ofcatfish.